Teaching Cisneros in India: Post(?)colonial Parables - Dittmar, Linda (Radical Teacher, 2015)
Setting: As Fulbright grants put it, I was a “cultural ambassador” to India twice, 1994-95 and 2009-10, but what exactly does being a “cultural ambassador” mean?